CULTURAL DISCONTINUITY : THE DISPERSED OF CHINESE DESCENT FROM THE “LITTLE CHINA” CHINATOWNS OF LASEM - Mukh. Imron Ali Mahmudi; Lugina Setyawati Setiono (Jurnal Sosiologi Nusantara, 2021)
This article aims to analyze how fading the Chinese diaspora culture from Lasem Chinatown over several generations. Previous studies show that Chinese descent's identity and orientation disappeared due to assimilation with the local community during the new order. In fact, there was a tendency for them not to show their Chinese identity from the beginning. This did not pay enough attention to the local context, social situation, and the cultural heritage of Chinese descent between generations. This case study is conducted by interviews, observation, and document study. The data is analyzed using the NVivo Program. Bauböck & Faist’s new concept of diaspora is used to review the phenomenon of the spread of Chinese descent from Lasem Chinatown. This research shows that the Indonesian Chinese people in Lasem tend to refer to themselves as 'Indonesian Chinese Peranakan and are increasingly detached from their identity relationship with their referent origin, China. Their Chinese identity is starting to fade since Chinese cultural heritage through religious rituals has been largely abandoned. Young Chinese children scattered out of Lasem Chinatown and lost their Chinese identity. The novelty in this research is that the assimilation and integration of Peranakan Chinese into local society are precisely related to the acceptance of the Lasem community, instead of Chinese culture's fading.Keywords: Chinese, Descent, Diaspora, Discontinuity, Dispersed